2018
DOI: 10.2174/1874088x01812010029
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization for the Synthesis of Silver (AgNPs), Iron Oxide (α-Fe2O3NPs) and Core-Shell (Ag-Fe2O3CNPs) Nanoparticles Using the Aqueous Extract of Alstonia Scholaris: A Greener Approach

Abstract: Objective:The present study is deals with the green synthesis of silver (AgNPs), iron oxide (α-Fe2O3NPs) and core-shell (Ag-α-Fe2O3CNPs) nanoparticles using the aqueous extract ofAlstonia scholariswithout any catalyst, template or surfactant or any intermediate under ultrasound cavitation technique. The purpose was to facilitate the high level of dispersion with increase in rate of reaction. Further AgNPs and α-Fe2O3NPs were used to synthesis Ag-Fe2O3CNPs in aqueous extract ofAlstonia scholarisunder controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…033-0664, respectively. The intensive peaks depicted fit the works of Shimpi et al [29] who synthesized core-shell Ag/Fe 2 O 3 NPs using an aqueous extract of Alstonia scholaris. By fitting the values to the Scherrer equation, the average size of the particle was found to be 39.59 nm.…”
Section: Crystallography Analysessupporting
confidence: 78%
See 2 more Smart Citations
“…033-0664, respectively. The intensive peaks depicted fit the works of Shimpi et al [29] who synthesized core-shell Ag/Fe 2 O 3 NPs using an aqueous extract of Alstonia scholaris. By fitting the values to the Scherrer equation, the average size of the particle was found to be 39.59 nm.…”
Section: Crystallography Analysessupporting
confidence: 78%
“…Additionally, the absorption bands around 1000 cm −1 were assigned to the C-N of aliphatic amines or alcohols/phenols [37] with absorption bands located around 1300 and 1600 cm −1 representing the symmetric and asymmetric bending modes of C = O bonds of amino acid and esters, respectively [30]. Finally, the broad peaks centred approximately around 2000, and 3400 cm −1 are associated respectively with standard H 2 O bending modes and OH stretching [29]. The temperature of the samples was kept constant at 300 K during the measurement.…”
Section: Vibrational Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the broadband at 3455 cm −1 for pure oxide while adding silver NPs does not cause a noticeable shift that O–H stretching vibration of the –OH group appears at 3448 cm −1 32 . The revealing absorption peak at 3554 cm −1 is assigned to thio-urea residual N–H stretching 33 . The Neodymium oxide (Nd 2 O 3 ) NPs strong band centered at 669 cm −1 is attributed to Nd–OH which shows significant diminishing with adding Silver nano-particles 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that the broadband at 3455 cm − 1 for pure oxide while adding silver NPs does not cause a noticeable shift that O-H stretching vibration of the -OH group appears at 3448 cm − 1 [14]. The revealing absorption peak at 3554 cm − 1 is attributed to thio-urea residual N-H stretching [15]. The Neodymium oxide (Nd 2 O 3 ) NPs strong band centered at 669 cm − 1 is attributed to Nd-OH which shows signi cant diminishing with adding Silver nano-particles [14].…”
Section: Ftirmentioning
confidence: 93%